Perancangan Sistem Rekomendasi Pemilihan Objek Wisata Karanganyar Dengan Metode Knowledge Base - Nugroho, Nur Cahyo; Moh. Muhtarom; Maulindar, Joni; Hartanti, Dwi (Infotek: Jurnal Informatika dan Teknologi, 2025)
Karanganyar Regency has significant potential in the tourism sector, especially nature tourism. However, the abundance of destination choices often makes it difficult for tourists to determine places that match their preferences. Currently available information is general and cannot be tailored to the specific needs of each user, making the decision-making process less efficient. This research proposes a knowledge-base recommendation system designed to assist users in selecting tourist destinations in Karanganyar according to their preferences. This system utilizes five main attributes: category, location, ticket price, rating, and facilities. System development was carried out using the Waterfall method, which includes requirements analysis and system design stages. User input is processed by matching it against the tourism data knowledge base using specific rules, and similarity calculations are performed to measure the degree of resemblance between user preferences and available tourism data. Based on similarity calculation results for 10 nature tourism data points, the system successfully recommended a destination with the highest similarity value of 0.991, namely Bukit Mongkrang, which best matched the user's selected criteria. Bukit Mongkrang met the user's desired criteria, being located in Tawangmangu, classified as nature tourism, having a mid-range ticket price, a rating 0.2 higher than the user's preference, and providing key facilities sought by the user. The results of this knowledge-base recommendation system modeling can serve as a reference for developing similar systems in the tourism field.